2019
DOI: 10.1111/1759-7714.12998
|View full text |Cite
|
Sign up to set email alerts
|

Improved efficacy of ramucirumab plus docetaxel after nivolumab failure in previously treated non‐small cell lung cancer patients

Abstract: Background It is unclear whether the chemotherapy response improves after exposure to immunotherapy. Antiangiogenic agents have been shown to stimulate the immune system and cause synergistic effects that stimulate tumor shrinkage. We conducted a retrospective study to evaluate improvement of the efficacy of ramucirumab plus docetaxel after the failure of nivolumab as a PD‐1 inhibitor. Methods From February 2016 to December 2017, 152 patients with non‐small cell lung ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
77
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(93 citation statements)
references
References 21 publications
6
77
1
Order By: Relevance
“…DTX or DTX + RAM was also recently reported to achieve a higher response rate as a subsequent chemotherapy after nivolumab compared to that without prior nivolumab treatment [18,19]. In this study, DTX + RAM showed a preferable response rate in ORR among the common regimens.…”
Section: Effectivenessmentioning
confidence: 50%
“…DTX or DTX + RAM was also recently reported to achieve a higher response rate as a subsequent chemotherapy after nivolumab compared to that without prior nivolumab treatment [18,19]. In this study, DTX + RAM showed a preferable response rate in ORR among the common regimens.…”
Section: Effectivenessmentioning
confidence: 50%
“…Shiono et al showed that, after nivolumab treatment, DOC+RAM therapy is highly effective (6). The ORR of DOC+RAM was reported to be 60%, and the PFS and OS were 169 and 343 days, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that treatment with immunotherapy does not condition the efficacy of subsequent chemotherapy. On the contrary, these studies seem to suggest an increase in the efficacy of chemotherapy [40][41][42][43][44], particularly when combined with anti-angiogenic agents [45][46][47], when administered after treatment with immunotherapy. Synergistic activity in both preclinical [48,49] and clinical models [21,22,25,26] support a hypothesis of a possible chemosensitization after prior exposure to immunotherapy.…”
Section: Discussionmentioning
confidence: 92%